2011
DOI: 10.1097/jto.0b013e3181f8a1bd
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Stroma in Cancer Progression and Prognosis: Emphasis on Carcinoma-Associated Fibroblasts and Non-small Cell Lung Cancer

Abstract: Maintenance of both normal epithelial tissues and their malignant counterparts is supported by the host tissue stroma. The tumor stroma mainly consists of the basement membrane, fibroblasts, extracellular matrix, immune cells, and vasculature. Although most host cells in the stroma possess certain tumor-suppressing abilities, the stroma will change during malignancy and eventually promote growth, invasion, and metastasis. Stromal changes at the invasion front include the appearance of carcinoma-associated fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
488
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(512 citation statements)
references
References 126 publications
12
488
1
11
Order By: Relevance
“…Moreover, the effect of matrix stiffening on fibroblast density was dominant or comparable with that due to mitogenic cues present in serum up to 0.5% FBS, which is a more physiologic concentration than the 10% to 20% FBS used in many cell culture studies. All these findings strongly support that matrix stiffening alone may be as important as soluble growth factors in driving fibroblast accumulation in vivo, thereby challenging the current view of stromagenesis as driven by paracrine signaling only (3,(8)(9)(10). Moreover, they extend previous evidence of a positive feedback loop in which activated fibroblasts lay out increased amounts of fibrotic ECM components that render a stiffer ECM, which in turn may drive fibroblast activation and accumulation further (11,14).…”
Section: Discussionmentioning
confidence: 32%
See 2 more Smart Citations
“…Moreover, the effect of matrix stiffening on fibroblast density was dominant or comparable with that due to mitogenic cues present in serum up to 0.5% FBS, which is a more physiologic concentration than the 10% to 20% FBS used in many cell culture studies. All these findings strongly support that matrix stiffening alone may be as important as soluble growth factors in driving fibroblast accumulation in vivo, thereby challenging the current view of stromagenesis as driven by paracrine signaling only (3,(8)(9)(10). Moreover, they extend previous evidence of a positive feedback loop in which activated fibroblasts lay out increased amounts of fibrotic ECM components that render a stiffer ECM, which in turn may drive fibroblast activation and accumulation further (11,14).…”
Section: Discussionmentioning
confidence: 32%
“…The current paradigm of TAF accumulation based on repairlike processes (3,(8)(9)(10)) supports a therapeutic strategy to reduce their density based on inhibiting stromal growth factors. Our data support the latter strategy in ADC-TAFs but not in SCC-TAFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor stroma also serves as a drug delivery barrier. Without the ability to overcome the tumor stromal barrier, the majority of delivered nanoparticles are sequestered at the perivascular areas [101]. To overcome the physical barrier of the stroma in drug delivery, theranostic nanoparticles targeting uPAR that is highly expressed in both cancer cells and tumor-associated stromal cells have been developed and their antitumor effects have been examined in a human pancreatic cancer xenograft model in nude mice.…”
Section: Chemotherapeutic Agent Deliverymentioning
confidence: 99%
“…Reactive stroma is found in most cancers and is typified by the coevolution of myofibroblasts (5)(6)(7). Importantly, the volume of reactive stroma relative to cancer is predictive of the rate of cancer progression in several tumor types (8)(9)(10)(11)(12)(13)(14)(15). Furthermore, in vivo modeling has shown that reactive stroma is tumor-promoting (16)(17)(18)(19).…”
mentioning
confidence: 99%